Synthesis and characterization of novel copolymers based on carbazole and anthracene, for optoelectronic applications - Belghiti, N.; Bouachrine, M.; Alimi, K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The goal of this work is to study a new copolymer which combines the Ecbz properties and those Ant. First, we describe the route for preparing the new copolymer. Then, we report characterization measurements based on solid-state Nuclear Magnetic Resonance (CP-MAS 13C NMR), Raman, IR absorption, UV–visible absorption, photoluminescence spectroscopy, Scanning Electron Microscopy (SEM), and X-ray diffraction.